Evaluation of a novel tissue stabilization gel to facilitate clinical sampling for translational research in surgical trials. Issue 2 (January 2015) - Sutton, P. A.; Jones, R. P.; Morrison, F.; Goldring, C. E.; Park, B. K.; Palmer, D. H.; Malik, H. Z.; Vimalachandran, D.; Kitteringham, N. R.
<x xml:space="preserve">Abstract</x> Background The aim was to establish the feasibility of using a tissue stabilization gel (Allprotect™) as an alternative to liquid nitrogen to facilitate collection of clinical samples for translational research. Methods Tumour samples from patients undergoing surgery for primary or metastatic colorectal cancer were either snap‐frozen in liquid nitrogen or stored in Allprotect™ under a number of different conditions. Sample integrity was compared across different storage conditions by assessing biomolecule stability and function. DNA quality was assessed spectrophotometrically and by KRas genotyping by pyrosequencing. Total RNA retrieval was determined by nanodrop indices/RNA integrity numbers, and quality assessed by reverse transcription–PCR for two representative genes (high‐mobility group box 1, HMGB1; carboxylesterase 1, CES1) and two microRNAs (miR122 and let7d). Western blot analysis of HMGB1 and CES1 was used to confirm protein expression, and the metabolic conversion of irinotecan to its active metabolite, SN‐38, was used to assess function. Results Under short‐term storage conditions (up to 1 week) there was no apparent difference in quality between samples stored in Allprotect™ and those snap‐frozen in liquid nitrogen. Some RNA degradation became apparent in tissue archived in Allprotect™ after 1 week, and protein degradation after 2 weeks. Conclusion In hospitals that do not have access to liquid nitrogen and –80°C freezers, Allprotect™ provides a suitable alternative for the acquisition and stabilization of clinical samples. Storage proved satisfactory for up to 1 week, allowing transfer of samples without the need for specialized facilities. <boxed-text content-type="box" id="bjs9678-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance Access to clinical material is a fundamental component of translational research that requires significant infrastructure (research personnel, liquid nitrogen, specialized storage facilities). The aim was to evaluate a new‐to‐market tissue stabilization gel (Allprotect™), which offers a simple solution to tissue preservation without the need for complex infrastructure. Allprotect™ offers comparable DNA, RNA and protein stabilization to tissue snap‐frozen in liquid nitrogen for up to 1 week. Degradation of biomolecules beyond this highlights its role as a short‐term tissue preservative. Allprotect™ has the potential to increase surgeon participation in translational research and surgical trials requiring tissue collection. </boxed-text>